Pharmacology examination & board review / Anthony J. Trevor, Bertram G. Katzung, Marieke Kruidering-Hall, Susan B. Masters. - Trevor, Anthony J.; Katzung, Bertram G.; Kruidering-Hall, Marieke; Masters, Susan B. (New York : McGraw-Hill Medical, 2013)
Delivers a clear, concise review of fundamental concepts backed by more than 1,000 review questions and answers.
Basic principles -- Autonomic drugs -- Cardiovascular drugs -- Drugs with important actions on smooth muscle -- Drugs that act in the central nervous system -- Drugs with important actions on blood, inflammation, & gout -- Endocrine drugs -- Chemotherapeutic drugs -- Toxicology -- Special topics.
Previous ed.: 2010.
"A Lange medical book."
Includes bibliographical references and index.
Pharmacy
Keywords: Pharmacology -- Examinations -- Study guides; Pharmacology -- Examination Questions